ANXIETY OF DINAH MORRIS IN GEORGE ELLIOT'S ADAM BEDE: A PSYCHOANALYTIC APPROACH - INDRIYANTI , TUTI (2007)
The major problem of this research is how the major character solves her inner conflict based on her conscience. The objectives of the study are to analyze the novel based on its structural elements and to analyze it based on psychoanalytic approach. In analyzing Adam Bede, the writer uses psychoanalytic approach and qualitative method. The object of the study is the personality of the major character of Dinah Morris. Adam Bede was published in 1959 by the Pocket Library. The data sources are literary data that are divided into two categories, primary and secondary data sources. The primary data source is the novel Adam Bede itself and the secondary data collection of the study is library research. The technique of data analysis is descriptive analysis. The outcome of the study shows that the problem faced by the major character causes the conflict of her mental condition. It brings her in anxiety which influences her decision-making process. Finally, the decision is taken as the influence of her conscience.